2020
DOI: 10.1051/0004-6361/202037496
|View full text |Cite
|
Sign up to set email alerts
|

Chemical equilibrium in AGB atmospheres: successes, failures, and prospects for small molecules, clusters, and condensates

Abstract: Chemical equilibrium has proven extremely useful for predicting the chemical composition of AGB atmospheres. Here we use a recently developed code and an updated thermochemical database that includes gaseous and condensed species involving 34 elements to compute the chemical equilibrium composition of AGB atmospheres of M-, S-, and C-type stars. We include for the first time Ti x C y clusters, with x = 1-4 and y = 1-4, and selected larger clusters ranging up to Ti 13 C 22 , for which thermochemical data are ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 290 publications
(442 reference statements)
7
107
1
Order By: Relevance
“…The values of f 0 (SO) range between < 6.8×10 −8 and 6×10 −6 and have a mean fractional abundance of log f 0 (SO) = -6.1 ± 0.6. Chemical equilibrium calculations predict a peak SO abundance in the 1-10 R region of ∼ 10 −7 (Agúndez et al 2020), while nonequilibrium chemical models considering shocks induced by the pulsation of the star predict similar abundances at 5 R (Cherchneff 2006). Therefore, on average, our observed SO abundances are higher than theoretical predictions of the inner wind.…”
Section: Somentioning
confidence: 49%
See 2 more Smart Citations
“…The values of f 0 (SO) range between < 6.8×10 −8 and 6×10 −6 and have a mean fractional abundance of log f 0 (SO) = -6.1 ± 0.6. Chemical equilibrium calculations predict a peak SO abundance in the 1-10 R region of ∼ 10 −7 (Agúndez et al 2020), while nonequilibrium chemical models considering shocks induced by the pulsation of the star predict similar abundances at 5 R (Cherchneff 2006). Therefore, on average, our observed SO abundances are higher than theoretical predictions of the inner wind.…”
Section: Somentioning
confidence: 49%
“…Thermochemical equilibrium calculations predict that SiO maintains a uniform and high fractional abundance of several 10 −5 from the photosphere out to 10 R in O-rich CSEs, while in C-rich CSEs the predicted fractional abundance from 5 R is also on the order of 10 −5 . The main difference occurs in the innermost region, from the photosphere to around 5 R , where SiO has a low abundance in C-rich conditions while it maintains a high abundance in O-rich CSEs (Agúndez & Cernicharo 2006;Agúndez et al 2020). In a scenario of chemical equilibrium, it seems that the low SiO abundance within 5 R in C-rich CSEs does not have an influence on the final SiO abundance that is injected into the expanding wind, and that chemical equilibrium holds for SiO in the high abundance region located beyond 5 R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the O-and C-rich parent species of Papers I and II, we compiled two observationally motivated sets for C-rich outflows. These are based on Agúndez et al (2020), who have compiled (ranges of) observed abundances of parent molecules in C-rich, O-rich, and S-type stars (see their Table 2). One set uses the mean of the ranges in observed abundances, as an approximation of an average C-rich outflow.…”
Section: Observational Grids Of Agb Outflowsmentioning
confidence: 99%
“…Most of these molecules have been found in the millimeter range, where molecules without a permanent dipole moment cannot be observed due to their lack of a pure rotational spectrum. One of them is CO 2 , which is predicted to be an abundant parent species by chemical models (e.g., Cherchneff 2006;Agúndez et al 2020) with abundances related to H 2 of 10 −8 −10 −4 . The detections in AGB stars carried out to date have only been done from space with the Infrared Space Observatory (ISO) and the Spitzer Space Telescope (e.g., Justtanont et al 1996Justtanont et al , 1998Ryde et al 1997;Tsuji et al 1997;Yamamura et al 1999;Cami et al 2000;Markwick & Millar 2000;Sloan et al 2010;Smolders et al 2012;Reiter et al 2015; Baylis-Aguirre et al 2020) as a consequence of the extremely high atmospheric opacity.…”
Section: Introductionmentioning
confidence: 99%